2012
DOI: 10.1097/olq.0b013e31823e67a9
|View full text |Cite
|
Sign up to set email alerts
|

Is Optimism Enough? Gay Men's Beliefs About HIV and Their Perspectives on Risk and Pleasure

Abstract: HIV optimism remains a useful indicator of gay men's likelihood to take risk, but technical knowledge, experience, desire, and attitudes to risk may all affect how people respond and often in multiple, sometimes contradictory, directions. Men's beliefs about HIV transmission risk in particular may reflect willingness to pursue pleasure over risk, or, alternatively, morbid fear of any risk. Measures of HIV optimism should be complemented by analysis of the complexities of individuals' assessments of both risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 6 publications
2
40
0
Order By: Relevance
“…Themes also show that the relative meaning of risk and pleasure or adventure was pursued, constructed and reinforced by the men and their networks. Separate research has also observed that many gay men make similar assessments about risk and pleasure within this understanding of relative risk, often reflecting their own pre-existing perspectives about desire and risk [26]. This resonates with sentiments from Beck and colleagues of a 'risk society' [27][28], referring to a set of social, political and cultural conditions within which the men constructed and experienced risk in their daily lives.…”
Section: Discussionmentioning
confidence: 88%
“…Themes also show that the relative meaning of risk and pleasure or adventure was pursued, constructed and reinforced by the men and their networks. Separate research has also observed that many gay men make similar assessments about risk and pleasure within this understanding of relative risk, often reflecting their own pre-existing perspectives about desire and risk [26]. This resonates with sentiments from Beck and colleagues of a 'risk society' [27][28], referring to a set of social, political and cultural conditions within which the men constructed and experienced risk in their daily lives.…”
Section: Discussionmentioning
confidence: 88%
“…These were based on earlier measures,18 with such items as ‘HIV is less serious than it used to be’ and ‘HIV treatments take the worry out of sex’. Responses were on a four-point scale ranging from ‘strongly disagree’ to ‘strongly agree.’ Scores were assigned where ‘one’ was least optimistic and ‘four’ was most optimistic.…”
Section: Methodsmentioning
confidence: 99%
“…We think the diminished threat of HIV (and greater optimism about avoiding transmission) as a result of treatments has contributed to the rise in condomless sex, although it is by no means the only explanation. 16,34,39 The increase in condomless sex between casual male partners appears to be the main reason that HIV notifications have increased among GBM in Australia. 11,13 This is despite the increase in HIV treatment and undetectable viral load, the decline in partner numbers, the relatively high level of ongoing condom use and the increase in use of risk-reduction strategies such as serosorting during condomless anal sex.…”
Section: Discussionmentioning
confidence: 99%